(untitled) (Research, Society and Development, 2024)
Introduction: The sleep-wake cycle works in a circadian rhythm and is fundamental for preserving the functions of the human organism. Various endogenous and exogenous factors can affect this cycle. Objective: To elucidate the relationship between anxiety disorders and changes in sleep patterns. Methodology: This is an integrative review on the association between anxiety disorders and sleep disturbances. Data was used from the Virtual Health Library (VHL), Scientific Electronic Library of Medicine (SciELO) and National Library of Medicine (PubMed) databases, using the descriptors “sleep disorders”, “anxiety disorders”, “circadian rhythm” and “sleep deprivation” to answer the question formulated using the PICO strategy. Results and Discussion: There are different sleep disorders and they can affect any stage of sleep, be it wakefulness, REM sleep or NREM sleep. The relationship between these disorders and anxiety is a two-way street, as they can exacerbate anxious feelings at the same time as anxiety leads to sleep problems. Cognitive-behavioral therapy, psychoeducation and drugs are the strategies most often used to treat anxiety and sleep disorders, but further research is needed into alternative methods, such as the use of cannabidiol, noise, medicinal plants and manual therapy. Conclusion: In view of the damage caused by the association between anxiety and sleep disorders, it is necessary to elucidate this relationship and look for new treatments that guarantee a better quality of life for affected patients.